VARIOUS APPROACHES TO THE THEORY OF INTRODUCTORY PARTS OF THE SENTENCE IN MODERN LINGUISTICS (World Bulletin of Social Sciences, 2024)
Different words and constructions combine with each other creating structural and semantic unity between parts of sentences. And sentences make semantic sequence to create the text. A sentence is a unit of speech whose grammatical structure conforms to the laws of the language and which serves as the chief means of conveying a thought. It is not only a means of communicating something about reality but also a means of showing the speaker’s attitude to it. This article outlines the different approaches to the introductory parts of the sentences, the main function of which shows the speaker’s attitude to the sentence.
Keywords: Parts Of The Sentences; Syntactic Function; Syntactic Relations